The US Role in the World Manufacturing and Trade as a Global Issue - V. G. VARNAVSKIY (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
The article considers the USA role and place in the global  manufacturing and trade. Key aspects of the world economy  transformation in the context of globalization, internationalization  and liberalization are studied. As shows, USA and China are the two  largest economies in the world. United States is the world’s largest  economy by nominal GDP and second largest by purchasing power  parity (PPP). It holds a 15.4 percent share of global GDP in PPP  (2016). China is the world’s largest economy by PPP, accounting for  17.8 percent of global GDP. The USA share of world GDP declined by  a total of 3.8 percentage points between 2006 and 2016. At the  same time, the United States possesses great economic strength. It  is also the world leader in innovation. China’s success has mostly  been in lowerend innovation. This country has been less successful in  higher-end innovation, where USA currently maintain a lead. The  United States holds a leading position in aerospace, instrument  making, cloud computing, ICT, robotics-related technologies, nanomaterials, biopharmaceutical and other high-tech  industries and China significantly lags behind. Special attention is paid to the U.S. foreign trade. It is shown that the USA is one of  the world’s largest importer and exporter of goods and services. It  accounts for 10.5 percent of global goods and services exports in  2016 (second place after China) and 13.3 percent of global imports  (first place). Despite the world’s second place after China in some economic indexes such as gross domestic product (at PPP),   size of manufacturingand merchandise trade, USA ranks first in the  world in terms of quality indicators of economic development. It  remains the most powerful economy in the world. The author’s  conclusion is that, the loss of US world leadership in terms of output  indicators has not yet become a global problem for other countries  and world economy in the whole.